Curvularia lunata on brown leaf spot of rice (MR220 CL2) / Nur Hakimah Wahab and Intan Sakinah Mohd Anuar - Wahab, Nur Hakimah; Mohd Anuar, Intan Sakinah (Faculty of Plantation and Agrotechnology, 2018)
Rice is a vital source in Malaysia as a staple food and major revenue to some of smallholder farmer especially in Northern Peninsular Malaysia. Rice also contribute a huge amount of carbohydrate content to its consumer make it essential in community daily life. However, the emergence of destructive diseases like brown leaf spot disease in rice field cause the decreasing in yield and supply produce to consumer. The high demand from the consumer call for the best solution to control the disease. In this study, Trichoderma species was used as a biological control agents to control brown leaf spot cause by Curvularia lunata. The aims of these study were to isolate C. lunata and characterize based on morphological characteristics and pathogenicity test and to determine the inhibition between Trichoderma spp. and C. lunata by using dual culture method. Based on morphological characteristics and pathogenicity test, five isolation were confirmed as C. lunata. Meanwhile, the application of Trichoderma in all five isolutions C. lunata was showed more than 50 percent growth inhibition of C. lunata on the seven days at incubator. TC4 isolate showed the highest inhibition of Trichoderma which controlled the growth of C. lunata with 83.87 percent. The percentage inhibiton radial growth (PIRG) that more than 50 percent indicates that Trichoderma species as good biological control. Therefore, these species should play an important role in control of brown leaf spot disease of rice which safer and also reduce negative impact on soil organisms and environment.